Microwave absorption properties of holey graphene/silicone rubber composites. (15th February 2018) - Chen, Chun-Yu; Pu, Nen-Wen; Liu, Yih-Ming; Chen, Li-Hang; Wu, Chia-Hung; Cheng, Tsai-Yi; Lin, Ming-Hsien; Ger, Ming-Der; Gong, Yann-Jang; Peng, You-Yu; Grubb, Peter M.; Chen, Ray T.
Abstract: The complex permittivity and return loss (RL) for the composites of silicone rubber filled with holey graphene nanosheets (HGNS, prepared by ultra-rapid heating during the step of thermal reduction/exfoliation of graphite oxide) were measured in the 3–18 GHz range. HGNS-based composites were found to have significantly higher microwave absorption than composites incorporating other types of graphene reduced at lower heating rates. Even with only 1 wt.% loading, its experimentally measured RL reached −32.1 dB at 13.2 GHz with a thickness of 2 mm, and simulation suggested that at a thickness of 3 mm its RL can be as low as −45.3 dB at 7.8 GHz. Material characterization indicated that the density of the holes increased with the temperature ramp rate, and the hole sizes ranged from 5 to 300 nm. Compared to other graphene samples, HGNS possessed significantly larger specific surface area and higher density of defects, suggesting that defect-induced losses, interfacial polarization, and multiple reflection/scattering at the interfaces are the major loss mechanisms. Our simple and low-cost process as well as the very low loading ratio of HGNS are advantageous for cost reduction in future applications. Graphical abstract: Image 1 Highlights: The microwave absorption properties of holey graphene/silicone rubber composites are reported. At 1 wt.% loading of holey graphene, a return loss of −45.3 dB at 7.8 GHz was achieved. A contactless free-space microwave measurement system, which offers reliable and reproducible results, was employed. Holey graphene's numerous defects and large surface area were the key factors for its excellent microwave absorption. The low filler loading promises good potential for lightweight, low-cost microwave absorbers.